Characterization of spinel bubbles and preparation and properties of lightweight ceramics. Issue 5 (1st March 2021) - Chen, Zhening; Chen, Huizi; Yang, Hui; Wang, Jiabang
Abstract: During the selection of materials for anti-lithium ion corrosion, magnesium aluminate spinel has been found to have good corrosion resistance and low cost. During the preparation of light-weight spinel ceramics, it is considered to be kiln body material. In this work, spinel bubbles were prepared using electrofusion injection process. Bulk density, volume density and pressure resistance of spinel bubbles in different particle sizes were counted. Light-weight spinel bubble ceramics with different densities were prepared by using electrofused spinel bubbles as light aggregates and using ρ-Al2 O3 and caustic burnt magnesia powder as matrix powders. The microstructure of spinel bubbles with different particle sizes and light spinel ceramics was analyzed using scanning electron microscope. Results show that the spinel bubble has complete structure, good sphericity, perfect grain crystallization, and clear edges and corners. Although there are some fine cracks and cavities, grains are tightly bound. Compressive strength and bending strength of light-weight spinel ceramics, whose density were found to lie within the range of 0.99–1.63 g cm −3, were found to be 5.19–36.33 MPa and 3.48–12.84 MPa, respectively.